2004
DOI: 10.1042/bj20031456
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of androgen receptor transcriptional activity by the nuclear receptor co-repressor (N-CoR)

Abstract: Antiandrogens are widely used agents in the treatment of prostate cancer, as inhibitors of AR (androgen receptor) action. Although the precise mechanism of antiandrogen action is not yet elucidated, recent studies indicate the involvement of nuclear receptor co-repressors. In the present study, the regulation of AR transcriptional activity by N-CoR (nuclear receptor co-repressor), in the presence of different ligands, has been investigated. Increasing levels of N-CoR differentially affected the transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 44 publications
3
37
1
Order By: Relevance
“…Upon binding to DNA, sequences found in the NTD (called activation function 1 ) and LBD (AF-2) facilitate activation of transcription. Genetic and biochemical experiments have indicated that the LBD of AR interacts with the NTD upon ligand binding (7,14,27,32,82), which is similar to the results observed for the ER (39). This intramolecular interaction has been shown to be important for optimal receptor activity (7,12,14,32,82).…”
supporting
confidence: 60%
“…Upon binding to DNA, sequences found in the NTD (called activation function 1 ) and LBD (AF-2) facilitate activation of transcription. Genetic and biochemical experiments have indicated that the LBD of AR interacts with the NTD upon ligand binding (7,14,27,32,82), which is similar to the results observed for the ER (39). This intramolecular interaction has been shown to be important for optimal receptor activity (7,12,14,32,82).…”
supporting
confidence: 60%
“…In contrast, we find little polymerase II bound to the promoter in the presence of flutamide. This observation in the tumor is consistent with cell culture studies showing that Casodex may actively repress the PSA gene by permitting androgen receptor to interact with corepressors (32,43,44). In addition, flutamide decreases the association of androgen receptor with various coactivators including TIF2, which in turn affects androgen receptor -mediated transcriptional activity (43,45).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, DHT and bicalutamide treatment resulted in DJ-1-AR colocalization throughout the nucleus, whereas DJ-1-AR seemed to concentrate just inside the nuclear perimeter after OH-flutamide treatment. These differences may be due to the well-characterized AR T877A substitution mutation in LNCaP cells (32)(33)(34). This mutation allows flutamide to exhibit agonist activity; however, because this mutation causes an AR conformational change, it could inhibit the interaction with DJ-1.…”
Section: Discussionmentioning
confidence: 99%